Puddling of butterflies in Jahangirnagar University campus and the bank of Bangshi river, Savar, Bangladesh - Rima, Nourin; Meme, Afroza; Hossain, Md Monwar (Jahangirnagar University Journal of Biological Sciences, 2016)
Butterfly is one of the amazing creatures of nature, which possesses some interesting behavior like puddling that includes feeding at mud, dung or carrion. A total of 54 species of butterflies under 8 families were found to gather around two different puddle grounds viz. Jahangirnagar University campus (JU campus) and bank of Bangshi river (BBR), Savar, Dhaka during January 2012 to December 2013. Among the recorded 54 species of butterflies, 6 species belonged to the family Papilionidae, 11 species to Pieridae, 10 species to Lycaenidae, 3 species to Danaidae, 13 species to Nymphalidae, 7 species to Satyridae, 3 species to Hesperiidae and 1 species to Acraeidae. In JU campus several types of puddling sources were used by butterflies viz. mud or wet soil, dung, carrion, wet sands and wet bricks, human sweat, bird-dropping, rotten fruits and flowers. On the other hand, in the bank of Bangshi river, butterflies used polluted water on the river side. In those puddle sources, members of Papilionidae and Pieridae were preferred mineral sources as they did puddle on mostly water sources (mud, wet soil, wet sand, wet brick), while members of Nymphalidae, Hesperiidae and Lycaenidae preferred to puddle on various nutrient sources (carrion, dung, rotten flowers). These results indicated that butterfly require various minerals and nutrients which are extracted through puddling sources for their reproductive success and other physiological activities. Jahangirnagar University J. Biol. Sci. 5(1): 57-70, 2016 (June)